God-talk prayer as communi-action - Crizaldo, Rey Lemuel Papa (2009.)
"Nearly every definition of prayer refers to some type of communication phenomenon, yet research that treats it as a legitimate communication phenomenon is still wanting. This study responds to the need to understand prayer and the meaning that an individual ascribes to it from the standpoint of communication theory. It explores the performance of individual personal prayer as a communication experience among the youth of the three major Protestant groups in the Philippines (i,e., the Fundamentalists, the Evangelicals and the Liberals). The distinctive prayer traditions of the three groups were compared noting specifically the intricacies and motivations involved as well as the influence of one's faith community to the act. How the performance of personal prayer relates to being a form of intrapersonal and interpersonal communication is given prime consideration. Qualitative methods such as document analysis, keye informant interviews, intensive individual interviews, and focus group discussion were employed in the study. The findings indicate that one's faith community does have an impact on how personal prayer is performed and experienced. Responses reveal that prayer is experienced as an authentic and genuine form of dialogue with an unseen being. While prayer seems to touch aspects of both intrapersonal and interpersonal dimensions of communication, certain dynamics involved suggest the need for a "spiritual communication" framework."
Thesis (M.A. Communication Research)--University of the Philippines, Diliman.
Vita.
Keywords: Communication -- Religious aspects -- Philippines; Youth -- Religious aspects -- Philippines; Spiritual life